A review of adverse events in animals and children after secondary exposure to transdermal hormone‐containing medicinal products. Issue 1 (28th October 2022) - Sjöström, Karin; Mount, James; Klocker, Anna‐Karin; Arthurson, Veronica
Abstract: Background: Hormonal replacement therapy is widely used to treat conditions in humans, the most well‐known indication being the relief of menopausal symptoms in women. Many of the hormone‐containing products (HCP) are applied to the skin. This transdermal delivery poses a risk to animals and humans through secondary exposure, especially when product information is not strictly followed. The aim of this article is to raise awareness among veterinarians and human healthcare providers of this risk; based on evidence from spontaneous reporting of suspected adverse events (AEs) in animals and humans. Interventions are also explored to mitigate the risk of secondary exposure to transdermal HCP (THCP). Review of spontaneously reported suspected AEs: The Swedish Medical Products Agency has received several, mainly serious, AE reports in animals and children following secondary exposure to THCPs. The AE reports were reviewed together with worldwide data from the EudraVigilance Veterinary database and human EudraVigilance Data Analysis System. The clinical signs reported in animals included persistent signs of oestrus, poor growth rate and birth defects. In humans, reported clinical signs included precocious puberty, unresolved virilisation, accelerated growth rate and female infertility. Conclusions: It is important that THCP are used according to manufacturer's instructions and users are made aware of risks and mitigating measures. This review of AEs in animals and children provides evidence to show that the use of THCP poses a risk for secondary exposure. Efficient communication strategies that stretch across veterinary and human medicinal disciplines are required to raise mutual awareness and minimise the risk of AEs in animals and humans.